2014
DOI: 10.1063/1.4876234
|View full text |Cite
|
Sign up to set email alerts
|

Continuously-tuned tunneling behaviors of ferroelectric tunnel junctions based on BaTiO3/La0.67Sr0.33MnO3 heterostructure

Abstract: In this work, we fabricate BaTiO3/La0.67Sr0.33MnO3 (BTO/LSMO) ferroelectric tunnel junction on (001) SrTiO3 substrate by pulsed laser deposition method. Combining piezoresponse force and conductive-tip atomic force microscopy, we demonstrate robust and reproducible polarization-controlled tunneling behaviors with the resulting tunneling electroresistance value reaching about 102 in ultrathin BTO films (∼1.2 nm) at room temperature. Moreover, local poling areas with different conductivity are finally achieved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In the present work, FTJs were studied theoretically, where the set of the related parameters were obtained from the fitting and are presented in Table 1. J−V characteristics were simulated according to the developed model (5). The comparison of the simulated S1−S4 with related experimental data is shown in Figures 3a, 4, 5a, and 6a, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, FTJs were studied theoretically, where the set of the related parameters were obtained from the fitting and are presented in Table 1. J−V characteristics were simulated according to the developed model (5). The comparison of the simulated S1−S4 with related experimental data is shown in Figures 3a, 4, 5a, and 6a, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent experiments, the M1/FE/M2 FTJ stack systems were employed to study the thickness effects of the FE layer, and it was demonstrated that FE properties do exist in ultrathin films. It was found that ferroelectricity exists even for single-unit-cell-thick perovskite FE layers according to quantum effects and lattice strain. , FEs possess an internal electric field due to the spontaneous polarization of dipole moments, inducing finite opposite electric fields ( E -fields) in both left and right metallic interfaces that form, so-called, screening regions. , These screening regions are characterized by screening lengths (λ L , λ R ) and screening amplitudes of the potential energy profile of the barrier (δ V 1 , δ V 2 ) for the left M1/FE and right FE/M2 interfaces, respectively. The potential interfacial energy profile might provide a large difference for tunnel transparency, resulting in two resistive states of the FTJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18], the coercive field was about 1.0 Â 10 9 V m À1 for 2 nm-thick BaTiO 3 films; in Ref. [19], for 1.2 nm-thick BaTiO 3 , the coercive field was as . It is reasonably possible that the coercive field of the 1 nm-thick BaTiO 3 film proposed here will be even larger.…”
Section: à2mentioning
confidence: 99%
“…Thin BaTiO 3 films have been shown to retain ferroelectric properties down to one-unit cell thickness theoretically [16], and 0.8 nm experimentally [17]. More importantly, it is already clear that the coercive field of BaTiO 3 films increases with decreasing film thickness below 3 nm [11,18,19].…”
mentioning
confidence: 98%